Art Work Cities, Identities, and Cultural Work - Durey, Matthew J. (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
This book is about the relationship between art and work in the cultural economy. It is an exploration of the experiences of people working in cultural and creative industries, and of the importance of place, identity, and culture in postindustrial society. Drawing on fieldwork exploring the conditions of cultural work, identity, and postindustrial cities in Newcastle upon Tyne, UK and Hamburg, Germany, the book argues that the conditions of work in the cultural economy are the result of a contradictory tension between art and economy, which manifests in various ways in artists' conditions of work, their identities, and their relationship to the changing landscapes of postindustrial cities. This is explored through a series of stories from people working in cultural and creative industries, in which they highlight significant contradictions, obstacles, and opportunities in negotiating the cultural economy, casting light on the importance of art and culture in postindustrial society.
Introduction -- Identities -- Cultural Work -- Cities -- Newcastle -- Hamburg -- The Dialectic of Art and Economy -- Conclusions.
Keywords: Human geography; Sociology; Anthropology; Geography; Human Geography; Sociology; Anthropology; Regional Geography